Parâmetros toxicológicos em carpas (Cyprinus carpio) expostos a formulações comerciais de diferentes herbicidas em condições de lavoura de arroz e em laboratório - Moraes, Bibiana Silveira (2008)
Pesticides can affect toxicological parameters and cause oxidative stress in fish. In Brazil there are few studies linking pesticide toxicity with fish. For this reason, two experiments were conducted to evaluate possible effects of herbicides on some toxicological parameters in carp (Cyprinus carpio). The fish were exposed to two commercial herbicides, one composed of a mixture formulated imazetapir and imazapic and the second composed of clomazone. The periods of exposure were seven days in the laboratory and seven, 30 or 90 days on rice field condition. After the experimental period, metabolic and toxicological parameters in the liver, brain and muscle tissues were evaluated. The enzymatic parameters analyzed in different tissues of this species were acetylcholinesterase activity (AChE), catalase (CAT) and glutathione S-transferase (GST). Also, oxidative stress parameters, such as carbonyl protein and TBARS levels in hepatic tissue, were analyzed. The metabolic parameters analyzed in liver and muscle of carp were glucose, glycogen, lactate, protein, amino acids and ammonia. Moreover, metabolic assessments were made (glucose, lactate and protein) in carp plasma. The results showed that AChE activity was increased in carp brain after seven days of exposure to a commercial formulation containing imazethapyr and imazapic herbicides both under field and laboratory conditions. In the same period of exposure, muscle tissue showed reduced activity of AChE after exposure to all herbicides (imazetapir and imazapic and clomazone) under laboratory conditions. At 30 days, in the field, AChE activity was reduced in brain and enhanced in muscle of carps exposed to imazethapyr and imazapic. Fish exposed to clomazone herbicide did not show any change in the activity of this enzyme in this period. On the other hand, at 90 days of exposure, only the fish exposed to the herbicide clomazone, showed a reduction in muscle AChE activity. The antioxidant enzyme catalase showed increased activity in liver tissue after seven days of exposure under both experimental conditions. At 30 days of exposure, catalase activity showed no further changes and after 90 days of exposure activity was reduced in liver of carp exposed to clomazone herbicide. The enzyme glutathione S-transferase was altered only after 30 and 90 days of exposure in the field. GST activity was reduced in liver tissue after exposure to both herbicides tested. TBARS levels were increased in almost all periods, terms of exposure and tissues considered, with the exception of brain tissue, which presented a decrease in TBARS levels at 30 days of exposure. Protein carbonyl was reduced in liver of carp exposed to clomazone herbicide after seven days under laboratory conditions. Moreover, at 30 and 90 days of exposure, the protein carbonyl levels were increased in the liver of fish exposed to both herbicides. After exposure to both herbicides, the carp showed metabolic disorders. In general, protein and amino acid levels were reduced and the amount of glycogen was enhanced in liver and muscle of carp exposed to both herbicides at all times tested. However, ammonia, lactate and glucose levels were increased and reduced according to the tissue considered, time of exposure and herbicide tested. These results indicate that the parameters measured may be good indicators of contamination of these commercial herbicides in Cyprinus carpio.